1997
DOI: 10.1038/sj.cdd.4400265
|View full text |Cite
|
Sign up to set email alerts
|

Energy supply and the shape of death in neurons and lymphoid cells

Abstract: Apoptosis and necrosis are considered as conceptually distinct forms of cell death. Nevertheless, there is increasing evidence that classical apoptosis and necrosis represent only the extreme ends of a wide range of possible morphological and biochemical deaths. The two classical types of demise can occur simultaneously in tissues or cell cultures exposed to the same stimulus, and often the intensity of the same initial insult decides the prevalence of either apoptosis or necrosis. This suggests that, while so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 92 publications
9
60
0
Order By: Relevance
“…This scenario would be compatible with the finding that many drugs induce necrosis at high doses and apoptosis at lower (`subnecrotic') doses (Kroemer, 1995). It would also be compatible with the observation that modulation of ATP levels can shift the balance between apoptosis and necrosis to one or the other mode of cell death (see accompanying reviews by Nicotera and Leist, 1997;Tsujimoto, 1997). Finally, it would explain why cells in which the activation of most if not all caspases is inhibited by means of the inhibitor Z-VAD.fmk (N-benzyloxycarbonyl-Val-Ala-Asp-fluromethylketone) undergo nonapoptotic (necrotic?)…”
Section: Inducer Of Ptsupporting
confidence: 70%
“…This scenario would be compatible with the finding that many drugs induce necrosis at high doses and apoptosis at lower (`subnecrotic') doses (Kroemer, 1995). It would also be compatible with the observation that modulation of ATP levels can shift the balance between apoptosis and necrosis to one or the other mode of cell death (see accompanying reviews by Nicotera and Leist, 1997;Tsujimoto, 1997). Finally, it would explain why cells in which the activation of most if not all caspases is inhibited by means of the inhibitor Z-VAD.fmk (N-benzyloxycarbonyl-Val-Ala-Asp-fluromethylketone) undergo nonapoptotic (necrotic?)…”
Section: Inducer Of Ptsupporting
confidence: 70%
“…Depletion of intracellular ATP by incubating cells in glucose-free medium to halt glycolysis, in the presence of the mitochondrial F 0 F 1 -ATPase inhibitor oligomycin, completely blocked apoptosis induced by Fas stimulation, VP16, dexamethasone or calcium ionophore, and ATP supplied through either glycolysis or mitochondrial oxidative phosphorylation restored the apoptotic cell death pathway, indicating that apoptosis is ATP-dependent . The same conclusion was also reached by (discussed by Nicotera and Leist, 1997). Shimizu et al, (1995d), measured intracellular ATP levels during cell death, and shown that intracellular ATP levels remain unchanged until the very end of apoptotic process such as disruption of plasma membrane.…”
Section: Atp An Intracellular Determinant Of Cell Death By Apoptosissupporting
confidence: 65%
“…Cell shrinkage, DNA damage, chromatin condensation and blebbing of the plasma and alteration of plasma membrane phospholipid organisation with phosphatidylserine externalisation are major characteristics of apoptosis (Williams, 1991;Wood and Youle, 1994). Necrosis is generally characterised by swelling of cells and mitochondria, scattered chromatin condensation and loss of plasma membrane integrity because of an overwhelming physical cell injury (Williams, 1991;Nicotera and Leist, 1997).…”
Section: Discussionmentioning
confidence: 99%